2011
DOI: 10.1159/000329625
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus-Infected Decoy Cells in Cytocentrifuged Urine Cytology Specimens from Renal Transplant Recipients

Abstract: Objective: To evaluate the prevalence of BK virus (BKV) infection in renal transplant recipients based on the detection of urinary decoy cells. Methods: Fifty transplantation patients (56% males) aged 39.9 ± 11 years were screened for urinary decoy cells. The majority (86%) had received grafts from living donors. The inclusion criteria were graft dysfunction, hematuria, and/or leukocyturia. Creatinine and urea serum levels were monitored for 6 months. Results: Decoy cells were found in the urine of 12 (24%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
1
4
0
2
Order By: Relevance
“…The 32% prevalence of detection of decoy cells found in this study is within the range of 16.9 to 37.5% reported in other Brazilian studies [16][17][18][19] . Few Brazilian studies used molecular assays to determine the prevalence of BKV infection among transplant recipients [13,20] .…”
supporting
confidence: 85%
“…The 32% prevalence of detection of decoy cells found in this study is within the range of 16.9 to 37.5% reported in other Brazilian studies [16][17][18][19] . Few Brazilian studies used molecular assays to determine the prevalence of BKV infection among transplant recipients [13,20] .…”
supporting
confidence: 85%
“…At nine months post-transplantation, 32.5% of patients were found to have BKV viremia, but only 8 (4%) developed BKVAN. Previous studies performed in Brazil showed higher frequencies of BKVAN in kidney transplant recipient, 20 , 21 which may be related to differences in screening strategy (e.g., urinary decoy cells to trigger additional urine/plasma sampling for qPCR), in addition to regular biopsies, and ischemia times. The most relevant implication of BKV infection in renal transplant recipients relies on its ability to lead to graft fibrosis, which can be followed by renal dysfunction and eventually lead to graft loss.…”
Section: Discussionmentioning
confidence: 91%
“…However, the use of noninvasive techniques such as urine cytology for decoy cells [35] can facilitate the selection of patients at higher risk for BKVN, which could lead to the loss of the graft.…”
Section: Discussionmentioning
confidence: 99%